Simulation numérique du plissement des tôles lors de leur transport en continu dans les usines sidérurgiques - Jacques, Nicolas; Elias, Akli; Potier-Ferry, Michel; Zahrouni, Hamid (European Journal of Computational Mechanics, 2006)
The development of plastic creases, called wrinkles, during sheet metal conveying in processing lines is considered. Finite element analyses are carried out to modelize wrinkling when a sheet is passing over a roll. A description of this phenomenon is proposed. When a strip is stretched, small compressive stresses occur near the roll and cause the strip buckling. Simulations have shown that friction between sheet and roll accentuates the postbuckling patterns during strip displacement. In some cases, buckles evolve to create a wrinkle by a plastic cumulative mechanism.